Free vibration analysis of functionally graded graphene platelet-reinforced metal foam doubly curved panel - Zhang, Li-Li; Zhao, Li-Cai; Lang, Song-Jun; Asemi, Kamran (Frontiers in Materials, 2024)
In this research, free vibration characteristics of functionally graded metal foam doubly curved panels reinforced with graphene platelets and with porosities have been surveyed. Halpin Tsai's approach is utilized for extracting the effective Young modulus of porous metal foam nanocomposite and also the effective density of nanocomposite porous doubly curved shell panel is estimated by using an extended rule of mixture. The FSDT hypothesis is utilized for determining the displacement field and the Finite element and Hamilton principle are utilized for deriving the mass and stiffness matrices of the structure. Finally, the influences of several variables such as porosity distribution, porosity coefficient, GPL dispersion pattern, the weight fraction of Nanofillers, and span angles on the free vibrations characteristics of doubly curved shell panels with FG porosities and reinforced by graphene platelet have been reported in detail.